Colour Preference by Penaeus indicus in Feeding - P.M., Aboobaker; A., Noble (Fishery Technology, 2025)
Experiments on feeding behaviour of Indian white prawn, (Penaeus indicus H. Milne Edwards) indicate highly significant preference to bright colours in the order of red, green and yellow overwhite and dark shades. As colour of food appears to attract the prawns, colour- ing the diet is suggested to have application in better feed management.